A rapid method for evaluating the edible oil oxidative stability during ambient storage by FTIR spectroscopy using a mesh cell. Issue 25 (16th June 2016) - Xu, Lirong; Yu, Xiuzhu; Liu, Lei; Li, Mengjun; Zhang, Rui
Abstract : Changes of functional group spectra of edible oils during oxidation on a mesh cell. Abstract : A rapid method for evaluating the edible oil oxidative stability during ambient storage was established by Fourier transform infrared (FTIR) procedures, using a mesh cell as the spectral acquisition accessory. The prepared oil samples were exposed to visible light at ambient temperature (23 ± 2 °C), and the oxidative stability of edible oils was predicted by comparing the time when the peroxide value (PV) reached 20 and 100 meq. kg −1 by using the mesh cell-based oxidation method (MCOM) and bulk oxidation. The results indicated that the MCOM is 2.6 to 4.2 times faster than the oxidized oils in bulk when the PV reached 20 and 100 meq. kg −1, respectively. The oxidation changes in some functional groups can be monitored in real time during ambient storage using the mesh cell-based FTIR technique. Compared with traditional oxidation methods, the use of the mesh cell-based FTIR technique provides a simple, practical, and rapid means for evaluating the oxidative stability of edible oils during ambient storage.